Analisis Pemanfaatan E-Commerce di Masa Pandemi Covid-19 pada UMKM Db Wood Kota Surabaya - Ananda Riana Wulansari Widjanarko; Indrawati Yuhertiana (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine knowledge about the use of using E-Commerce and the condition of income using E-Commerce during the Covid-19 pandemic. The research approach used is a qualitative phenomenological approach. Data was collected in descriptive form, namely by collecting data obtained from informants in the form of interviews. The results of the analysis of the use of E-Commerce in an effort to increase income during the Covid-19 pandemic can be concluded that DB Wood's MSME actors interpret E-Commerce knowledge by seeing opportunities to dare to open a business at the beginning of the pandemic, planning strategies, and maintaining consumer satisfaction to increase income. E-Commerce also provides effectiveness and time efficiency. DB Wood's MSME income has increased as seen from product sales reaching 3,000 products sold. It can be said that the use of E-Commerce-based digitalization can maximize revenue growth during the Covid-19 pandemic.